Mechanistic insight into the selective hydrogenolysis of sorbitol to propylene glycol and ethylene glycol on supported Ru catalysts. Issue 19 (8th June 2016) - Jia, Yuqing; Liu, Haichao
Abstract : Ru/C efficiently catalyzes the selective hydrogenolysis of sorbitol to ethylene glycol and propylene glycol in the presence of Ca(OH)2 . This reaction proceeds by primary dehydrogenation of sorbitol to hexose intermediates as the rate-determining step, most likely via preferential activation of its C(5)–H bond on the Ru surfaces. Abstract : Supported Ru clusters efficiently catalyzed the selective hydrogenolysis of sorbitol to ethylene glycol and propylene glycol in the presence of Ca(OH)2 . Ru/C was more selective to the two target glycols than Ru catalysts on MgO, Al2 O3, ZrO2 and TiO2 with similar Ru particle sizes (∼2 nm). The reaction parameters, including the amount of Ca(OH)2, H2 pressure and temperature, strongly influenced the activity and selectivity of Ru/C, which reflects the bi-functional requirements of sorbitol hydrogenolysis that involves the competitive Ru- and base-catalyzed reactions of ketose or aldose intermediates, derived primarily from sorbitol dehydrogenation. Kinetic isotopic studies with different deuterated sorbitols confirmed that such a sorbitol dehydrogenation step was kinetically relevant to the hydrogenolysis reaction, which most likely proceeded by preferential activation of its C(5)–H bond on the Ru surfaces, as indicated by the more noticeable kinetic isotope effect with sorbitol deuterated at its C-5 position than those at the other C positions. Moreover, it was found that the hydrogenolysis of hexitols with different configurations showed large differences in their activities and selectivities. Erythro sequences of the vicinal hydroxyl groups adjacent to the primary carbons in the hexitol molecules, compared to threo sequences, tended to facilitate the hydrogenolysis reaction and the formation of C3 products over C2 products, most likely as a result of the effects of the different sequences of the hydroxyl groups on the adsorption and C–H bond activation of hexitols on Ru. Clearly, these findings and understanding demonstrate the feasibility of effective synthesis of ethylene glycol and propylene glycol from sorbitol and other largely available polyols, for example, by rational design of more efficient catalysts and tuning of polyol adsorption configurations.